2014
DOI: 10.1186/s40529-014-0071-5
|View full text |Cite
|
Sign up to set email alerts
|

Hyphoderma pinicola sp. nov. of H. setigerum complex (Basidiomycota) from Yunnan, China

Abstract: BackgroudHyphoderma setigerum (Fr.) Donk is a white-rot wood-decaying corticoid fungal species. It occurs worldwide from tropical to temperate regions. However, taxonomic studies in recent decades showed that H. setigerum is a species complex with four separate species, before this study.ResultsHyphoderma pinicola sp. nov. was collected on dead wood of Pinus yunnanensis Franch. in the temperate montane belt at 2200–2400 m altitudes, in Yunnan Province of China. Within the H. setigerum complex this new taxon is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 12 publications
0
14
0
Order By: Relevance
“…As well as with two sequences from GenBank under H. setigerum from the USA, and clade 5 (Nilsson et al 2003 ) from China and Japan under H. nudicephalum . On the other hand, H. setigerum s.str and H. subsetigerum (clades 7A and 7B) from Nilsson et al ( 2003 ) grouped close to H. pinicola described from China by Yurchenko and Wu ( 2014 ).
Fig.
…”
Section: Taxonomymentioning
confidence: 65%
See 1 more Smart Citation
“…As well as with two sequences from GenBank under H. setigerum from the USA, and clade 5 (Nilsson et al 2003 ) from China and Japan under H. nudicephalum . On the other hand, H. setigerum s.str and H. subsetigerum (clades 7A and 7B) from Nilsson et al ( 2003 ) grouped close to H. pinicola described from China by Yurchenko and Wu ( 2014 ).
Fig.
…”
Section: Taxonomymentioning
confidence: 65%
“…Based on molecular, morphological and crossing test analyses, Nilsson et al ( 2003 ) concluded that H. setigerum is a species complex and nine taxa exist inside it. Moreover, a succession of studies (Gilbertson and Blackwell 1988 ; Wu 1997 ; Boidin and Gilles 2003 ; Yurchenko and Wu 2014 ) described four more species with this type of cystidia: Hyphoderma nudicephalum from Louisiana, USA, Hyphoderma subsetigerum from Taiwan, Hyphoderma bisetigerum from Madagascar, and Hyphoderma pinicola from China.…”
Section: Taxonomymentioning
confidence: 99%
“…and Å. Strid, H. pinicola , H. rimulosum , H. setigerum , H. sibiricum (Parmasto) J. Erikss. and Å. Strid, H. sinense , H. subclavatum , H. subsetigerum Sheng H. Wu, H. transiens, and H. membranaceum [ 8 , 18 , 25 , 27 , 29 , 40 , 41 , 46 ]. Further studies should focus on the relationships between the host and Hyphoderma species, as well as trying to better understand the evolutionary directions between plant and Hyphoderma species.…”
Section: Discussionmentioning
confidence: 99%
“…Alternaria alternata , which is a common dominant species in M, Q, and Y, has the ability to degrade cellulose and lignin (Guillen et al 1987 ; Sharma et al 2016 ). Fusarium solani in M, Mortierella elongata and Hyphoderma setigerum in Q, Nigrospora oryzae and Epicoccum nigrum in Y have been reported to have the ability to degrade lignocellulose (Lozovaya et al 2006 ; Olajuyigbe et al 2016 ; Yao et al 2012 ; Yurchenko and Wu 2014 ).…”
Section: Discussionmentioning
confidence: 99%
“…. Fusarium solani in M, Mortierella elongata and Hyphoderma setigerum in Q, Nigrospora oryzae and Epicoccum nigrum in Y have been reported to have the ability to degrade lignocellulose(Olajuyigbe et al 2016;Yao et al 2012;Yurchenko and Wu 2014). stress resistance, such as high temperature and low dissolved oxygen resistance, and the potential for lignocellulose degradation.…”
mentioning
confidence: 99%